Association between adolescent life events and depressive symptoms: data from the Shanghai area - Shuzhi Peng; Yan Wang; Xin Huang; Xin Zhang; Juan Ge (Frontiers in Psychiatry)
ObjectiveTo explore the relationship between adolescent life events and depressive symptoms and the influence of family factors.MethodsBased on the data of 766 adolescents in Shanghai, this study collected information by electronic questionnaire, and evaluated it by using the Adolescent Life Event Scale (ASLEC) and the Center for Epidemiologic Studies Depression Scale (CES-D).ResultsThe study found that there was a significant nonlinear relationship between life event scores and depressive symptoms, and two key inflection points were identified, 13 and 45.5. Teenagers with depressive symptoms are more likely to report poor family economic status and low education level of their mothers.ConclusionFamily factors play an important role in adolescent depression symptoms, and the research results provide a basis for preventing adolescent depression. In the future, it is necessary to expand samples and longitudinal studies to further verify the conclusions.